Globalization and economies: issues from the Global South - Asante, George; Bentil, Samuel; Kankam, Boadu; Bordoh, Anthony (Frontiers in Education, 2025)
Globalization is a crucial concept in the economics of the world today. It can be akin to the adage that “fire is a good servant but a bad master.” Globalization can foster an innovative, creative, and affluent economic environment, but can also lead to the growth of inequality, the widening of the poverty gap between and within countries, and environmental destruction. This study explores two hundred and fourteen tertiary students’ perspectives on globalization and the extent of its effects on the development of Ghana’s economy. The descriptive design was used with a questionnaire for data collection. The study revealed that students exhibit a strong association of globalization with key aspects such as cultural exchange, industrial development, technological advancement, and the movement of goods and people. The study also found that globalization leads to lower confidence in job creation, rising income inequality, and little overall benefits for developing economies. It recommends that Ghana carefully navigates the balance between its national policy priorities and global governance frameworks to enhance productive capacity, promote economic diversification, generate employment, and maintain a stable financial and investment environment.